Estrategias lúdicas para el aprendizaje de las tablas de multiplicar, que faciliten el proceso de enseñanza-aplicación en los estudiantes de la Unidad Educativa Darío C. Guevara de La Parroquia El Salto, cantón Babahoyo, Provincia de Los Ríos - Franco Fajardo, Evelyn Jahaira (2019)
The problem addressed is based on the fact of the absence of playful strategies by the teacher in the process of teaching and learning of mathematics. In this sense, the purpose of the research was to propose recreational strategies for learning the multiplication tables, which facilitate the teaching-application process in the students of the Darío C. Guevara Educational Unit of the El Salto Parish, Canton Babahoyo, Province from the rivers. The research was framed in a non-experimental field design, descriptive level in the form of a feasible project. Regarding the population, it was made up of the six teachers of the first grade. The technique applied was the survey and the instrument the questionnaire, it was validated by the expert opinion. The conclusions derived from the study allow to affirm the presence of a teaching and learning process where lacking the application of playful strategies in order to achieve the objectives planned to improve the knowledge of multiplication tables. However, teachers do recognize that the teaching of mathematics should be oriented in a practical way and through the use of the game, but they do not have the necessary strategies or do not know which one to apply. Reality that supports the proposal where a series of fun, relevant and fun strategies is revealed to provide meaningful learning by giving a contribution to the teaching and learning process of mathematics.